Optimal Sizing and Siting of PV and Battery Based Space Microgrids Near the Moon’s Shackleton Crater - Diptish Saha; Najmeh Bazmohammadi; Jose Maurilio Raya-Armenta; Angelina D. Bintoudi; Abderezak Lashab; Juan C. Vasquez; Josep M. Guerrero (IEEE Access, 2023)
Space mission cost and feasibility depend mainly on the size and mass of the payload. This paper investigates the optimal photovoltaic (PV) array and battery size and mass for an islanded PV-battery powered space microgrid (MG) at the lunar south pole. The PV arrays are considered to be installed on top of towers to increase solar energy harvesting. Considering the dependency of the generated power from PV arrays on the tower height, different tower heights of 10, 50, and 100 m are investigated. The paper presents the methodology to estimate the available power from the PV system using the information of illumination time-series at the location of potential sites with different tower heights. Besides, considering the power demand of several power-consuming units at different operating states, the power demand profile of the lunar base is generated. The optimal sizing of the PV and battery system for a 1-year horizon, without considering battery degradation, results in a total mass of approximately $1.5 × 10^{5}~\text{kg}$ to $3.5 × 10^{5}~\text{kg}$ with a tower height of 10 m depending on the solar illumination profiles at different sites. For a 5-year optimization horizon of the same sites with 10 m tower height and considering the battery yearly capacity degradation, total system mass ranges approximately from $\mathrm {2 × 10^{5}~kg}$ to $5.5 × 10^{5}~\text{kg}$ . Although increasing the tower height may considerably reduce the total size and mass of the battery and PV system, the mass of the PV tower will increase. Thus, a satisfactory trade-off in selecting the site location and tower height is required. In this regard, 15 highly illuminated sites at different locations and with different PV tower heights are assessed in this paper. To improve the reliability and flexibility of the power system, the multi-microgrid (MMG) concept is deployed to distribute the power-consuming units of the base among different MGs having their local energy production and storage systems. Finally, based on ...